Nanogenerators based on vertically aligned InN nanowires. Issue 4 (24th December 2015) - Liu, Guocheng; Zhao, Songrui; Henderson, Robert D. E.; Leonenko, Zoya; Abdel-Rahman, Eihab; Mi, Zetian; Ban, Dayan
Abstract : Piezoelectric nanogenerators (NGs) based on vertically aligned InN nanowires (NWs) are fabricated, characterized, and evaluated. Abstract : Piezoelectric nanogenerators (NGs) based on vertically aligned InN nanowires (NWs) are fabricated, characterized, and evaluated. In these NGs, arrays of p-type and intrinsic InN NWs prepared by plasma-assisted molecular beam epitaxy (MBE) demonstrate similar piezoelectric properties. The p-type NGs show 160% more output current and 70% more output power product than the intrinsic NGs. The features driving performance enhancement are reduced electrostatic losses due to better NW array morphology, improved electromechanical energy conversion efficiency due to smaller NW diameters, and the higher impedance of intrinsic NGs due to elevated NW surface charge levels. These findings highlight the potential of InN based NGs as a power source for self-powered systems and the importance of NW morphology and surface state in overall NG performance.